HUBUNGAN KESIAPAN ORANG TUA DENGAN KEMAMPUAN PSIKOMOTORIK SISWA DALAM PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 - Eko Cahyono; Eko Susetyarini; Endrik Nurrohman (Universitas Tribhuwana Tunggadewi, 2021)
COVID-19 is a type of virus that attacks the respiratory system, this virus is a family with SARS and MERS. The impact of this virus makes some countries force online learning, namely learning through internet social media, online learning has a very beneficial effect on the psychomotor aspects of students. The purpose of this study was to determine the relationship of parental readiness in online learning with students' psychomotor abilities. Subjects in this study were Mohammad Hatta elementary school students grade 3 and parents of students with 30 each. The parameters studied were online readiness including the provision of infrastructure tools, application systems, and online content. The parameters used for the psychomotor aspects of art and cultural materials and craft making a miniature house include the preparation stage, the process stage, the product. Data collection technique is observation using a Likert scale questionnaire. Data analysis using Pearson's task test. The results showed that the average readiness of parents during online learning in the provision of infrastructure tools was 73%, application systems 62%, online content 62%. The average value of psychomotor ability is 81%. The findings of this study are the correlation between parents 'readiness in online learning and students' psychomotor abilities (0.638 0.361)